Development and Application of the Sample Support in Transmission Electron Microscopy. Issue 2 (January 2021) - Pan, Hengyu
Abstract: Cryogenic electron microscopy is becoming an increasingly popular technology that allows us to observe the molecules in high-resolution details. With this refined way to study the structures in scientific researches, the observation of the molecules will be expected to make improvements. The conventional methods, such as the X-ray crystallography and the nuclear magnetic resonance spectroscopy, provide the basic observation of ground-state molecules and the measurement of various small molecules. But both of them contain flaws discovered in the continuing development process. Therefore, the application of cryo-EM becomes a broader area to explore. In this review, we will give an overall understanding of the cryogenic electron microscopy. We will discuss the intention behind the invention of the cryo-EM and introduce the main workflow of the experiments. In addition, we will discuss the methods to prepare the sample in a well-condition and compare them among different groups of experiments. More importantly, we will discuss the application of the graphene in cryo-EM and evaluate possible improvements in future development.